Neurophysiologic Profiling of At-Risk Low and Very Low Birth-Weight Infants Using Magnetic Resonance Imaging - Qi, Ying; He, Jingni (Frontiers in Physiology, 2021)
Low birth-weight (LBW) and very low birth-weight (VLBW) newborns have increased risks of brain injuries, growth failure, motor difficulties, developmental coordination disorders or delay, and adult-onset vascular diseases. However, relatively little is known of the neurobiologic underpinnings. To clarify the pathophysiologic vulnerabilities of such neonates, we applied several advanced techniques for assessing brain physiology, namely T2-relaxation-under-spin-tagging (TRUST) magnetic resonance imaging (MRI) and phase-contrast (PC) MRI. This enabled quantification of oxygen extraction fraction (OEF), global cerebral blood flow (CBF), and cerebral metabolic rate of oxygen (CMRO2). A total of 50 neonates (LBW-VLBW, 41; term controls, 9) participated in this study. LBW-VLBW neonates were further stratified as those with (LBW-VLBW-a, 24) and without (LBW-VLBW-n, 17) structural MRI (sMRI) abnormalities. TRUST and PC MRI studies were undertaken to determine OEF, CBF, and CMRO2. Ultimately, CMRO2 proved significantly lower (p=0.01) in LBW-VLBW (vs term) neonates, both LBW-VLBW-a and LBW-VLBW-n subsets showing significantly greater physiologic deficits than term controls (p=0.03 and p=0.04, respectively). CMRO2 and CBF in LBW-VLBW-a and LBW-VLBW-n subsets did not differ significantly (p>0.05), although OEF showed a tendency to diverge (p=0.15). However, OEF values in the LBW-VLBW-n subset differed significantly from those of term controls (p=0.02). Compared with brain volume or body weight, these physiologic parameters yield higher area-under-the-curve (AUC) values for distinguishing neonates of the LBW-VLBW-a subset. The latter displayed distinct cerebral metabolic and hemodynamic, whereas changes were marginal in the LBW-VLBW-n subset (ie, higher OEF and lower CBF and CMRO2) by comparison. Physiologic imaging may therefore be useful in identifying LBW-VLBW newborns at high risk of irreversible brain damage.